Nuclear power as a system good: Organizational models for production along the value-added chain - Ben Wealer; Christian R. von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Due to its technical complexity, the co-production of electricity generation and nuclear weapons, and its high fixed costs, nuclear power is a particularly complex commodity, which poses unusual challenges for state economic (or industrial, defense, innovation etc.) policy. As in other sectors, the question arises here, too, of an adequate division of private and public responsibilities, in other words "competition and planning", taking into account knowledge aspects, incentive structures, transaction costs and a fair distribution of revenues and burdens. The nuclear sector requires an upstream system of a knowledge base, institutional and physical infrastructure (sites, transport, waste storage, etc.) and legal and institutional infrastructure. In this paper we apply the "system good analysis" developed by Beckers et al. (2012) and Gizzi (2016) to the nuclear power sector and identify ideal-typical organizational models for the value-added stages of the so-called nuclear front-end (mining, conversion, enrichment, fuel fabrication), constructing nuclear power plants, decommissioning and long-term storage as well as the respective interfaces between these stages. The main purpose of this overview paper is to assign tasks, rights and duties to organizations ("stakeholders") at the various stages of the value chain and to define the interface problems. We use an institutional economics approach, which focusses on the provisioning decisions and production between public authorities and private actors. In addition to a general overview, we focus on the back-end of the nuclear energy value chain, the decommissioning of facilities and the short- and long-term disposal of radioactive waste.
Keywords: 330; nuclear power; organizational models; institutional economics; transaction cost; decommissioning; nuclear waste management